PENGARUH PENYULUHAN TERHADAP TINGKAT PENGETAHUAN DAN SIKAP REMAJA TENTANG SEKS PRANIKAH PADA SISWA SMK NEGERI 8 PADANG TAHUN 2017 - Milya Novera; Diana Arianti; Dela Septianingsih (LPPM Universitas Abdurrab, 2018)
Abstract Adolescence is one of the stages in an individual's life to reach adulthood. The problem of sexuality is very visible among teenagers. Based ond SKRRI 2012 survei, between 51-75% students in Padang City done devation of sexsual behavior. The purpose of this study is to determine the influence of counseling on the level of knowledge and attitudes of teens about premarital sex. This research is a quantitative research method that is pre-experimental design with one group of pretest-posttest design. The populations of this study are 589 students from XI grade of SMK, used cluster random sampling technique with the number of samples are 58 female students. This study was conducted at SMKN 8 Padang in 2017. The analysis was using dependent T-test. The result showed an increase in knowledge and attitudes of teens about premarital sex before and after getting the counseling with p value = 0,000 from it was 70.7% of adolescents had low level became 8.6%, 22,4% of adolescents had low medium level became 13,8% and also 6,6% of adolescents had high knowledge became 77,6% after being given the counseling, and The adolescent attitudes was 44,8% negative and was 55,2% positive before giving counseling became decreased became was 34.5% negative and was 65,5% positive after being given counseling. It can be concluded that there is an influence of counseling to level of knowledge and attitude of adolescents before and after getting the counseling about premarital sex. It is expected that the school for provide information and counseling program for youth through cooperation with local health agencies that health center care to increase knowledge and attitudes of adolescents about health specially the premarital sex that activities such as counseling at school for every month a specially since the beginning of the school orientation. Keywords: Knowledge, Attitude, Premarital ,sex, Adolescence ABSTRAK Remaja merupakan salah satu tahap dalam kehidupan individu untuk mencapai dewasa. Survei SKRRI 2012, siswa/i SMAN di Kota Padang melakukan penyimpangan perilaku seksual. Tujuan penelitian untuk mengetahui pengaruh penyuluhan terhadap tingkat pengetahuan dan sikap remaja tentang seks pranikah. Penelitian ini kuantitatif dengan menggunakan metode pre-eksperimental desaign dengan rancangan one group pretest-posttest design. Populasi penelitian siswa kelas XI SMK Negeri 8 Padang, teknik pengambilan sampel cluster random sampling dengan jumlah sampel 58 siswa. Penelitian dilaksanakan di SMK Negeri 8 Padang pada bulan Januari s/d Juli tahun 2017. Analisa secara univariat dan bivariat menggunakan uji T- test dependen. Hasil penelitian terdapat perbedaan pengetahuan dan sikap remaja tentang seks pranikah sebelum dan sesudah penyuluhan dengan p=0,0007,7% tingkat pengetahuan rendah menjadi 8,6%, 22,4% tingkat pengetahuan sedang menjadi 13,8% dan 6,9% tingkat pengetahuan tinggi menjadi 77,6% setelah diberikan penyuluhan. Sikap remaja 44,8% negatif dan positif 55,2% sebelum penyuluhan mengalami penurunan menjadi 34,5% bersikap negatif dan 65,5% bersikap positif sesudah diberikan penyuluhan. Dapat disimpulkan, ada pengaruh penyuluhan terhadap tingkat pengetahuan dan sikap remaja sebelum dan sesudah dilakukan penyuluhan tentang seks pranikah. Disarankan pihak sekolah untuk memberikan informasi atau penyuluhan lebih lanjut melalui kerjasama dengan instansi kesehatan setempat seperti puskesmas dan klinik swasta tentang kesehatan khususnya pencegahan seks pranikah sejak awal orientasi sekolah dan menjadi kegiatan rutin setiap bulan.